PENGARUH PENERAPAN KONSEP GREEN BUILDING TERHADAP KENYAMANAN PENGGUNA JASA DI TERMINAL BANDAR UDARA INTERNASIONAL BANYUWANGI - Safarin Dwi Cahyaningrum; Kifni Yudianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Banyuwangi International Airport is one of the airports in Indonesia that implements the concept of green building , where building details refer to structures and use environmentally responsible processes and efficient resources throughout the building cycle by emphasizing on architectural works that are not only able to provide physical needs but also consider environmental needs. With the implementation of the green building concept , it does bring many positive effects to the environment, but on the other hand, this concept also has a negative impact on the comfort of service users. This research was conducted to find out whether there is influence and how much influence is related to the application of the green building concept to the comfort of service users at the Banyuwangi international airport terminal. This study used quantitative research methods with a research instrument in the form of a questionnaire. The results of the study show that: 1) the concept of green building influences the comfort of service users at the Banyuwangi international airport terminal. 2) The concept of green building influences the comfort of service users at the Banyuwangi international airport terminal by 66.6%.